OCHRONA DRÓG PUBLICZNYCH PRZEZ URZĘDNIKÓW RZYMSKICH - Kamińska, Renata (Zeszyty Prawnicze, 2017)
Roman Magistrates’ Activity in Protection of the Public Roads Summary The article treats of the competences of the Roman magistrates responsible for the public roads. In the Republic the public roads, buildings, sewers and drains were the responsibility of the aediles and censors. They were helped by the quattuorviri viis in urbe purgandis and the duumviri viis extra urbem purgandis from some unknown date (probably Caesarian). The former were appointed only to the streets and roads in Rome, the latter outside the walls of the City. Occasionally, special commissioners were appointed. In the early Empire, when the censorship was effectively in desuetudeand the duumviri abolished by the emperor, it was mainly the aediles who had to deal with public roads as the part of their cura urbis. It was Augustus who initiated an important reform of the cura viarum. He established the curatores viarum to supervise the maintenance of the great trunk roads. It was a senatorial or equestrian office depending on the status of the road, at the beginning temporary, but later it converted into a regular office. In the provinces there were praeses provinciae or vicares who were in charge of the roads. In the municipia supervising the maintenance of the roads and streets belonged to the curia. Great number and variety of the offices supervising public roads in the Republic and the Principate confirm how important they were in the public life of Rome as well as in the private matter of individuals.